Another Improbable Occurrence. - Andrews, W. T. (The Accounting Review, 1974)
Abstract Presents a hypothetical situation which is helpful in teaching and establishing several basic concepts of accounting for beginning accountancy students. Concepts that can be derived from the fairy tale story; Information on relationship between assets and expenses; Suggestion that accounting entities and the owner of those entities must be clearly identified.